Diapycnal Fluxes of Nutrients in an Oligotrophic Oceanic Regime: The South China Sea. Issue 22 (18th November 2017) - Du, Chuanjun; Liu, Zhiyu; Kao, Shuh‐Ji; Dai, Minhan
Abstract: Nutrients from depth have been hypothesized as a primary source of new nutrients that sustain new productivity in oligotrophic oceans; however, the flux is challenging to quantify. Here we show for a first time in the oligotrophic South China Sea an extremely low diapycnal dissolved inorganic nitrogen (DIN) flux as 1.8 × 10 −4 mmol m −2 d −1 in the nutrient‐depleted layer (NDL) above the nutricline, where other nutrient supplies sustain the new production. Here higher phosphate and silicate fluxes relative to DIN than Redfield stoichiometry further indicate N‐limited biological productivity and additional removal of DIN by diatoms. Below the NDL across the nutricline to the base of euphotic zone, termed as nutrient replete layer, the DIN flux is three orders of magnitude larger and sufficient in supporting the export production therein. Here higher DIC flux relative to DIN than Redfield stoichiometry further infers DIC excess in the upper ocean. Key Points: The commonly ignored diapycnal advection induced by turbulent mixing is important in calculation of diapycnal nutrient fluxes The euphotic zone should be categorized into two distinct layers in terms of vertical nutrient fluxes in oligotrophic oceanic regimes The modulation of diapycnal nutrient fluxes on biological carbon pump in the upper ocean and air‐sea CO2 exchange was inferred